Parents’ Openness to Multilingualism Shapes Young Minds - Rosnani, Ismail; Noraisah Nurul Fatwa, Mohd Razali; Umi Kalsom, Masrom (UMPSA, 2025)
It was just after 9:00 AM on a sunlit Friday morning when the first echoes of laughter filled the halls of the Centre for Modern Languages (CML) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA). Inside, 59 bright-eyed children aged 10 to 12 gathered, not in the usual silence of a classroom, but in a lively mix of excitement, music, and the gentle hum of languages from far and wide. The NextGen Camp had begun, and with it, a quiet revolution was taking place in the hearts and homes of UMPSA families.